Comparison of FIR and IIR Filters for Audio Signal Noise Reduction - Sancho Harmalita Liu; Nabila Husna Sabrina; Hardson Hardson (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
An audio signal is often used as a medium for spreading information. However, this signal is easily disrupted by noise from the environment around which the signal is taken, so a filter is needed to eliminate it. In this article, sound signals will be filtered using two types of filters, namely FIR with Hamming window method and IIR with the Butterworth method. Both filters are applied as low pass types with a cut-off frequency of 4000 Hz and an order of 100. Both filters will be employed to filter a 5000 Hz generated audio noise. The SNR and execution time of the filtered signal will then be compared to determine which filter is more effective. The result shows that FIR filters perform better than IIR filters for filtering audio noise.